A single incision transaxillary thoracoscopic sympathectomy - Marić, Nebojša; Stanić, Vojkan; Ristanović, Aleksandar; Cvijanović, Vlado; Milisavljević, Slobodan (Vojnosanitetski pregled, 2014)
Background/Aim. Primary hyperhidrosis causes are unknown. The disorder begins in early childhood. It intensifies in puberty and maturity. It is equally present in both sexes. The symptoms exacerbate when the body temperature rises and due to emotional stimuli affecting the sympathetic nerve system. The aim of this study was to demonstrate that video-assisted thoracoscopic surgery (VATS) sympathectomy is a method for primary focal hyperhidrosis permanent treatment. The single incision method in properly selected patients maximizes the intervention effectiveness and minimizes aesthetic side effects. Methods. This prospective study analysed the findings in patients who had been operated on due to primary focal hyperhidrosis (face, palms, and armpits) using a single small transaxilarry incision in the third inter-rib space at the level of the anterior axillary line with two 5 mm flexible ports. All the patients, with T2–T5 thoracoscopic sympathectomy of the sympathetic chain using a single small incision in the third inter-rib space in the anterior axillary line, were analysed in the period from September 2009 to November 2010 regarding the postoperative morbidity and outcomes of the operation (clinical evaluation and visual analogue scale) with a view to assessing the effectiveness of the surgery conducted in this manner. Results. A total of 47 patients (18 men, 29 women), 18 to 48 years old (29 on average) had underwent 94 bilateral video-assisted thoracoscopic sympathectomies. The sympathectomy was indicated in cases of facial blushing and sweating (6.38%), palmary sweating (34.04%), axillary sweating (14.89%) or both palmary and axillary sweating (44.68%). The largest percentage of patients (98.6%) had left the hospital the following day. The postoperative 30 day’s mortality was 0 and the conversion into open surgery was not necessary. As for complications, there had been an occurrence of partial pneumothorax in two patients treated by means of exuflation and chest drain, and one case of unilateral transitory Horner’s syndrome. Quarterly and annual postoperative monitoring showed excellent aesthetic effects of the surgery without any residual pain. The complete withdrawal of hyperhidrosis symptoms was noted in 44 (93.62%) of the patients. The recurrence of symptoms following the initial regression was seen in 3 (6.38%) of the patients 12 months after the surgery, whereas the patients surgically treated as a result of facial hyperhidrosis saw a significantly increased sweating of feet. The quality of life improved in 45 (95.6%) of the patients. Conclusion. Single incision transaxillary thoracoscopic sympathectomy generates excellent aesthetic and functional results in patients with primary focal hyperhidrosis.